2022
DOI: 10.3389/fonc.2022.828814
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Protein-Based Risk Model and H3K4me3 Modification Characteristics in Lung Adenocarcinoma

Abstract: The role and mechanism of transmembrane proteins (TMEMs) in tumorigenesis remain unclear. Based on 4 independent cohorts containing 1,208 cases, we identified 3 TMEMs (TMEM273, TMEM164, and TMEM125), which were used to construct a risk model to predict the prognosis of LUAD. The two patterns based on the risk score exhibited a high degree of consistency with the characteristics of immune cell infiltration and epigenetic distribution. Patients with a low-risk score, characterized by an increased activation of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Until now, the functions of ZCWPW2 in tumors have not been fully studied. Fan et al revealed that a lower H3K4me3 level was associated with a poor prognosis for LUAD patients ( Fan et al, 2022 ), and we hypothesized that ZCWPW2 could maintain a higher level of H3K4me3 to play a tumor-suppressive role. Chromobox protein homolog 5 ( CBX5 ), which has been proven to be associated with silenced, heterochromatic regions of the genome and belongs to the reader of H3K9me3.…”
Section: Discussionmentioning
confidence: 94%
“…Until now, the functions of ZCWPW2 in tumors have not been fully studied. Fan et al revealed that a lower H3K4me3 level was associated with a poor prognosis for LUAD patients ( Fan et al, 2022 ), and we hypothesized that ZCWPW2 could maintain a higher level of H3K4me3 to play a tumor-suppressive role. Chromobox protein homolog 5 ( CBX5 ), which has been proven to be associated with silenced, heterochromatic regions of the genome and belongs to the reader of H3K9me3.…”
Section: Discussionmentioning
confidence: 94%
“…PRR11 is implicated in the regulation of Wnt expression, contributing to the proliferation and metastasis of HCC cells to some extent 38 . TMEM164, classified as a member of the transmembrane protein (TMEM) family, is characterized by its presence in various biological membranes and its independent influence on lung carcinoma prognosis 39 . The transmembrane protein 164 (TMEM164) has been shown to be involved in selective autophagosome formation during ferroptosis that is dependent on the ATG5 receptor 40 .…”
Section: Discussionmentioning
confidence: 99%
“…IRX2 belongs to the Iroquois homeobox gene family, and there is evidence that LUADs commonly exhibit hypermethylation of the IRX2 promoter region ( 67 ). In addition, Fan et al developed a risk model based on transmembrane proteins, such as TMEM125, and explored its relationship with immune cell infiltration profiles in the TME ( 68 ). The specific mechanisms underlying the effects of TMEM125 and IRX on the development of LUAD and its prognosis warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%